The influence of anthropometric variables in agility abilities of young basketball players - Begu, B.; Kryeziu, A. R.; Bahtiri, A. (Sport Science - International Scientific Journal of Kinesiology, 2018)
The aim of this research is the influence of anthropometric variables on successful realization of agility tests to 14-15 years of basketball players. In this research are tested 84 basketball players of 7 active cadet equips (groups)-males. Through the regressive analysis procedure where are foreseen 11 predictor anthropometric variables, while 2 agility test criteria. The results that are presented in the basic parameters show that anthropometric variables and agility tests have shown homogeneous distribution. Results of regression analysis variables body height, leg length and thigh circumference have a low impact with agility tests, while other anthropomorphic variables did not affect agility tests.